The scaffold nucleoporins SAR1 and SAR3 are essential for proper meiotic progression in Arabidopsis thaliana - Fernández-Jiménez, Nadia; Martinez-Garcia, Marina; Varas, Javier; Gil-Dones, Félix; Santos, Juan Luis; Pradillo, Mónica (Frontiers in Cell and Developmental Biology, 2023)
Nuclear Pore Complexes (NPCs) are embedded in the nuclear envelope (NE), regulating macromolecule transport and physically interacting with chromatin. The NE undergoes dramatic breakdown and reformation during plant cell division. In addition, this structure has a specific meiotic function, anchoring and positioning telomeres to facilitate the pairing of homologous chromosomes. To elucidate a possible function of the structural components of the NPCs in meiosis, we have characterized several Arabidopsis lines with mutations in genes encoding nucleoporins belonging to the outer ring complex. Plants defective for either SUPPRESSOR OF AUXIN RESISTANCE1 (SAR1, also called NUP160) or SAR3 (NUP96) present condensation abnormalities and SPO11-dependent chromosome fragmentation in a fraction of meiocytes, which is increased in the double mutant sar1 sar3. We also observed these meiotic defects in mutants deficient in the outer ring complex protein HOS1, but not in mutants affected in other components of this complex. Furthermore, our findings may suggest defects in the structure of NPCs in sar1 and a potential link between the meiotic role of this nucleoporin and a component of the RUBylation pathway. These results provide the first insights in plants into the role of nucleoporins in meiotic chromosome behavior.